Comparison of Interpretation between Pyrosequencing and Xpert MTB/RIF Assay in Multidrug-Resistant Tuberculosis - Linda Choerunnisa; Coriejati Rita; Anna Tjandrawati; Lidya Chaidir; Ida Parwati (Faculty of Medicine, Universitas Padjadjaran, 2020)
Indonesia is one of the countries with the highest multidrug-resistant tuberculosis cases in the world. Rapid molecular test using the Xpert MTB/RIF assay is one of the detection methods for MDR-TB. Early detection of MDR-TB is crucial for early initiation of treatment. However, Xpert MTB/RIF assay only detects the rpoB gene mutations associated with Rifampicin resistance. Recently, WHO recommends the use of Pyrosequencing, a DNA sequencing method that can detect not only the rpoB gene but also katG and/or inhA gene mutations associated with Isoniazid resistance. The aims of this study were to compare the interpretation between the two methods and to determine the differences in codon mutation position detection of the rpoB gene and mutation detection of the katG and/or inhA gene. This was a cross-sectional comparative observational study on patients ≥18 years old interpreted as RR-TB patients based on Xpert MTB/RIF assay results who had not received MDR-TB drugs at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Results showed there were 40 Rifampicin-resistant TB subjects interpreted by Xpert MTB/RIF assay while Pyrosequencing interpreted 30 MDR-TB, 9 RR-TB and one Isoniazid-resistant TB subjects in January - February 2020. The detection of rpoB gene codon mutation position between Xpert MTB/RIF assay and Pyrosequencing methods was not significantly different (p=0.389). Pyrosequencing had detected 27 katG gene mutations, 3 inhA gene mutations, one katG and inhA gene mutation. To conclude, Pyrosequencing can be used for accurate detection of Rifampicin and Isoniazid resistance in MDR-TB. Perbandingan Hasil Interpretasi antara Pyrosequencing dengan Xpert MTB/RIF Assay pada Multidrug-Resistant TuberculosisIndonesia merupakan salah satu negara dengan kasus multidrug-resistant tuberculosis terbanyak. Penegakan diagnosis MDR-TB saat ini menggunakan tes cepat molekular Xpert MTB/RIF assay sehingga pasien segera mendapatkan pengobatan. Namun Xpert MTB/RIF assay hanya mendeteksi mutasi gen rpoB penyandi resistansi Rifampisin. World Health Organization merekomendasikan Pyrosequencing, metode sequencing nukleotida yang dapat mendeteksi mutasi gen rpoB, gen katG dan/atau inhA penyandi resistansi Isoniazid. Tujuan penelitian ini adalah menentukan apakah kedua alat ini memberikan hasil interpretasi yang sama, apakah ada perbedaan deteksi posisi mutasi kodon gen rpoB dan apakah ditemukan mutasi gen katG dan/atau inhA. Penelitian ini merupakan studi observasional komparatif dengan rancangan cross-sectional. Subjek penelitian adalah pasien usia ≥18 tahun yang diinterpretasi RR-TB berdasarkan Xpert MTB/RIF assay di RSUP Dr. Hasan Sadikin Bandung dan belum mendapat pengobatan. Xpert MTB/RIF assay menginterpretasi 40 subjek Rifampicin-resistant TB sedangkan Pyrosequencing menginterpretasi 30 subjek MDR-TB, 9 subjek RR-TB dan satu subjek Isoniazid-resistant TB pada bulan Januari-Februari 2020. Deteksi posisi mutasi kodon gen rpoB antara Xpert MTB/RIF assay dan Pyrosequencing tidak berbeda bermakna (p=0,389). Pyrosequencing mendeteksi 27 mutasi gen katG, 3 mutasi gen inhA, satu mutasi gen katG dan inhA. Kesimpulan, Pyrosequencing dapat digunakan untuk deteksi resistansi Rifampisin dan Isoniazid pada MDR-TB secara lebih akurat.